Implementation of the D’PEk_Hil for Early Detection of Preeclampsia and Clinical Recommendations in Pregnant Women - Viola Violentina; Melyana Nurul W; Arwani; Umi Toifah; Khairulisni Saniati (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Early detection and the management provide strategic role to decide therapies for mothers with high risk of preeclampsia and to prevent further complication. Expert-consulting system-based application could accelerate the early detection of preeclampsia and provides immediate expert feedbacks. This research and development attempted to implement D’PEk_Hil application for early detection and provide preeclampsia recommendation. This quasi-experimental design used posttest only design with non-equivalent control group. The subjects were 28 midwives grouped into intervention group to receive D’PEk_Hil application, consisting of 14 midwives; and control group to receive Mother-Child handbook, consisting of 14 midwives. The researchers analyzed the data with independent t-test. D’PEk_Hil application, observed in the intervention group, yieleded an immediate diagnose provision with 435,46 ± 25,809 (seconds) while the control group was with 608,11 ± 62,756 (seconds), (p-value of 0.01). The intervention group had a speed of providing recommendation for 444,46 ± 25,809 (seconds) while the control group was 695,25 ± 62,756 (seconds), (p-value of 0.000). The results revealed significant mean differences of diagnosis provision speed and in terms of providing recommendation based on the diagnoses between the groups. The D’PEk_Hill implementation could improve the time efficiency to early detect and provide therapy recommendaitons for preeclampsia mothers.